2013
DOI: 10.1111/nep.12038
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy: Comparative yield of cranial versus caudal needle trajectory. An ex vivo analysis

Abstract: The proportion of cortical tissue in the core biopsy specimen using the caudad angle approach was statistically significantly higher, compared with the cephalad needle trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…In terms of needle direction, our study is in keeping with the findings of Caliskan et al who reported a low rate of complications with an ultrasound-guided “tangential” approach to renal biopsy in a pediatric population [11]. Karam et al reported on an ex vivo model comparing caudal to cranial angle of renal biopsies [12] and found that the number of glomeruli obtained depended on the biopsy direction. Another group proposed an equation to calculate the safe depth of renal biopsy [8], and this may allude to avoidance of the medulla.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of needle direction, our study is in keeping with the findings of Caliskan et al who reported a low rate of complications with an ultrasound-guided “tangential” approach to renal biopsy in a pediatric population [11]. Karam et al reported on an ex vivo model comparing caudal to cranial angle of renal biopsies [12] and found that the number of glomeruli obtained depended on the biopsy direction. Another group proposed an equation to calculate the safe depth of renal biopsy [8], and this may allude to avoidance of the medulla.…”
Section: Discussionsupporting
confidence: 90%
“…The reason for the higher rate of complications during the first period may be the difficult needle coordination between radiologist and nephrologists without needle guide; needle guide reduces sliding of the ultrasound transducer on slippery gel which makes the complex task of coordination and alignment of transducer plane and biopsy needle plane easier to perform. A better yield of cortex was reported with caudal angulations when compared with cephalad angulations of the needle in a study on porcine kidney biopsies [ 19 ]. All native kidney biopsies were performed from the lower pole with caudal angulations and transplant kidney biopsies from the upper pole with cephalad angulations.…”
Section: Discussionmentioning
confidence: 99%
“…Various larger studies have reported minor complication rates varying from 7.5 to 58.6% and major complications from 0.3 to 4.3% [ 19 – 22 ]. We have observed minor complications in 5.4% and major complication in 5.1% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study in terms of major complications, we had only one case that needed blood transfusion (1.6%) and 2 cases (3.3%) with urinary bladder hematoma needing irrigation. While numerous larger reports have stated rates of minor complications ranged between 7.5 and 58.6% while major complications between 0.3 and 4.3% [17].…”
Section: Discussionmentioning
confidence: 92%